The Effects of Counseling and Predictors of Pregnancy Outcomes in Women With Hyperemesis Gravidarum [316]. (May 2015) - Maltepe, Caroline; Popa, Mircea Vlad; Bertucci, Cassandra; Farine, Dan; Koren, Gideon; Nulman, Irena
Abstract : INTRODUCTION: Hyperemesis gravidarum affects up to 2% of pregnant women and is associated with adverse pregnancy outcomes. The effects of intensive counseling in these women are understudied. METHODS: Prospectively collected cohort of women who called the Motherisk Nausea and Vomiting of Pregnancy Helpline for symptom management counseling was included. The study group consisted of women with hyperemesis gravidarum and the control group consisted of women with varying degrees of nausea and vomiting of pregnancy severity. Both groups received counseling on dietary changes, pharmacotherapy, and psychological support. Statistical analysis included inferential statistics, correlations, and regression. RESULTS: The women with hyperemesis gravidarum (n=240) required and sought more counseling compared with the control group (n=290). The women with hyperemesis gravidarum were younger (30.8 compared with 32.6 years; P <.001), called in for counseling significantly later (13.4 compared with 8.7 weeks of gestation; P <.001), and experienced more prolonged and severe nausea and vomiting of pregnancy (31 compared with 27 weeks of gestation; P <.001). There were no differences in the duration of gestation, birth weight, or perinatal complications. The women with hyperemesis gravidarum breastfed longer (11.2 compared with 8.5 months; P =.02), and their infants reached their developmental milestones significantly earlier (crawling [7.9 compared with 8.4 months; P =.03], speech [9.9 compared with 11.7; P <.001], sitting unaided [5.9 compared with 6.3 months; P =.02]). The number of counseling sessions per week was a significant predictor for maternal weight gain ( P =.001). However, the severity of nausea and vomiting of pregnancy was a significant predictor for duration of gestation and child speech development ( P =.02 and P =.01, respectively). CONCLUSION: Timely provided counseling, balanced nutrition, pharmacotherapy, and emotional support were associated were more favorable outcomes in patients with hyperemesis gravidarum. More research is needed to study the relationship between the severity of nausea and vomiting of pregnancy and a child's developmental milestones.